Language use and medical outcomes : issues in assuaging patients’ concerns of pain during consultations - Hor, Felicia Xue Ting (Nanyang Technological University, 2020)
Medical education on aspects of patients’ experience of pain often offer recommendations for doctors on what to do from a bio-medical standpoint, but it remains unclear to what degrees these recommendations are translated into real-world applications. The communicative dimension is also oft neglected. Thus, there is a need to examine the interactional organization of a medical consultation about pain. This study will investigate how doctors attempt to assuage patients’ concerns of pain during medical consultations using five first-visit clinic consultation recordings from Tan Tock Seng Hospital’s (TTSH) Urology department. Some regular practices used by doctors include euphemistic re-assessment, asserting the minimal risk of the procedure, figurative description of diagnostic tools, provision of local anesthetic, particularizing pain experience to the patient, and relaying parallel experiences of other patients to patient’s own pain experience. Out of these six, the two practices – relaying parallel experiences of other patients to the patient’s own pain experience and particularizing pain experience to the patient seems be able to effectively assuage patients’ concerns of pain. This paper also suggests possible reasons for why doctors may have issues assuaging patients’ concerns and posits considerations for doctors on how to overcome obstacles like not having the personal experience of undergoing the scope when attempting to assuage patients’ concerns of pain.